INSTITUTE OF BATYRS IN KAZAKH SOCIETY - Laeg, Ahmadi; Dautbekova, M. (Journal of history, 2018)
In this article batyrs’ institution in Kazakh culture is considered as “phenomenon of Kazakh culture”. In 18th century and in the beginning of 19th centuries batyrs played in society significant political economic role. It has been analyzed the place of batyrs in society, their specific ideology as special social group, their stile of life based on their social obligations, tradition of military, social rules and ethics to regulate their relation with other social groups and other “estate” features. Their phenomenology includes in their contribution to unity of people, ability to organize people against enemies, oratory skills used for the future of state, unifying people in groups by mindik (thousands) and tumenbasy (ten thousands), in ability to encourage military and to give them self-confidence.